2006
DOI: 10.1021/ol060765x
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Catalyzed Si−B Addition to 1,3-Dienes:  Disproportionation in Lieu of Silaboration

Abstract: [reaction: see text] Upon attempted silaboration of acyclic 1- and 1,4-substituted 1,3-dienes, a new disproportionation reaction was discovered, yielding 1:1 mixtures of allylsilanes and dienylboranes. It was demonstrated that, as a key step in this new catalytic process, hydrogen is being transferred from one diene moiety to another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In 2006, Moberg et al . used nickel complexes (such as Ni(cod) 2 , or a complex prepared in situ from Ni(acac) 2 in the presence of DIBAL‐H and triethylphosphine) in the addition reaction of B–E to a linear 1,4‐substituted diene (Scheme ; Path I–III), and obtained a mixture of borylsilyllation products—borylsubstituted butadiene 126 , 129 , 132 and silyl‐substituted diene 125 , 128 , 131 .…”
Section: Preparation Of Boron‐substituted 13‐dienesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Moberg et al . used nickel complexes (such as Ni(cod) 2 , or a complex prepared in situ from Ni(acac) 2 in the presence of DIBAL‐H and triethylphosphine) in the addition reaction of B–E to a linear 1,4‐substituted diene (Scheme ; Path I–III), and obtained a mixture of borylsilyllation products—borylsubstituted butadiene 126 , 129 , 132 and silyl‐substituted diene 125 , 128 , 131 .…”
Section: Preparation Of Boron‐substituted 13‐dienesmentioning
confidence: 99%
“…In 2006, Moberg et al [104] used nickel complexes( such as Ni The same group proposedt he mechanism of Ni-catalyzed disproportionation of (E,E)-5,7-dodecadiene with as ilylborane process (Scheme 39). [104] The studies revealed that the key step in this new catalytic process was ah ydrogen transfer from one diene moietyt oa nother,ass hown in the Schemeb elow.…”
Section: Addition Of B-e To Linear 13-dienementioning
confidence: 99%
“…In contrast to the situation with linear 1,4-disubstituted 1,3-dienes, which provide 1:1 mixtures of dienylboranes and hydrosilylated products [20], only 1,4-silaborated adducts were obtained from the cyclic substrates. The product from addition of 2-(dimethylphenylsilyl)-4,4,5,5-tetrametyl-1,3,2-dioxaborolane to 1,3-cyclohexadiene was formed with 82% ee using a catalyst obtained by reduction of Pt(acac) 2 in the presence of a phosphoramidite with (R)-binaphthyl and dibenzylamino groups.…”
Section: Resultsmentioning
confidence: 82%
“…40 They also reported that related nickel-catalyzed reaction of (dimethylphenylsilyl)pinacolborane (1c) with acyclic 1,4-disubstituted butadiene resulted in the formation of dienylboranes and allylic silanes as major products. 41 Platinum-catalyzed 1,4-silaboration of conjugated enynes having bulky substituents at the alkynyl carbons was also reported by Moberg's group. 42 5.3 Three-Compornent Coupling of Silylborane, 1,3-Diene, and Aldehyde.…”
Section: Silaboration Of 13-dienementioning
confidence: 79%